(untitled) - Wajih Abdel Fattah Ahmed Matar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research investigates the metric music in the poetry of Ali Mahmoud Taha between his commitment to the Arab meter heritage represented in the music of Khalil bin Ahmed, in rhythms and rhymes, and the innovation that he introduced to this heritage represented by his use in many poetic meters in his poems, images that were not approved by this heritage, as well as In much of his poetry he did not adhere to the unified rhyme, for he varied the rhyming letter within the one poem, and did not adhere to the letter of the rhyme did not adhere to a single one, in many of the poems of the book. In his poetry we are in front of two forms, one of them: A traditional musical tradition that adheres to the single rhythm, the unified rhyme, the sketches and the defects that were approved by Khalil bin Ahmed. The other: is the new form in which he renewed rhythms and rhymes and used images that were not approved by the metric heritage, and from here the idea of ??the research was born, as the research deals with poetic searches in the poetry of Ali Mahmoud Taha Indicating the poems that came in Al-Khalil metric heritage and the poems that did not adhere to this hereditary and were subject of renewal.